A comprehensive nurse-led aftercare programme addressing post-burn sexual well-being of adult burn survivors: a randomised controlled trial - Jonathan Bayuo; Frances Kam Yuet Wong; Arkers Kwan Ching Wong; Prince Kyei Baffour; Loretta Yuet Foon Chung (BMC, 2024)
Abstract Background Sexual well-being is a key part of being human yet often remains shrouded in secrecy and poorly addressed in the clinical setting. The impact of burns and its long-term sequelae often lead to concerns regarding body image disturbance, self-esteem issues, and interpersonal challenges which can impact on an individual's sexual well-being. However, existing post-burn rehabilitation programmes usually lack components addressing concerns regarding sexual well-being. As a part of a larger project, we developed a nurse-led aftercare programme, and this study sought to examine the effects of the programme in addressing the post-burn sexual well-being of adult burn survivors. Methods A randomised controlled trial approach was used. Sixty burn survivors aged ≥ 18 years with burn size ≥ 10% total burn surface area were assigned to intervention and control groups. Participants in the intervention group underwent the nurse-led aftercare programme which involved pre-discharge support and proactive follow-up support over 8 weeks. The sexuality subscale of the Burn Specific Health Scale-Brief was used to evaluate the outcome of interest. Data were collected at three timepoints: baseline (T0), post-intervention (T1), and follow-up (T2). Results Using a corrected p value of 0.017, the study observed only statistically significant time effect at both T1 and T2. Both group and interaction effects were statistically insignificant for this outcome. Conclusion Issues regarding sexual well-being are often considered sacred and may be challenging to discuss. Thus, a longer duration of the intervention may be considered with ongoing training of practitioners to identify and resolve emerging challenges. Despite the non-significant interaction and group effects, including sexual well-being support in post-burns rehabilitation programmes will facilitate access to and utilisation of the service among burn survivors who may need it. Trial registration Prospectively registered on 14th August 2020. ClinicalTrials.govNCT04517721.